Key principles for country theory of change for food systems transformation anchored in CAADP strategic and action plan (2026-2035) - Ulimwengu, John M.; Mutyasira, Vine; Keizire, Boaz (Alliance for a Green Revolution in Africa, 2024)
Africa is at a pivotal moment in its journey toward achieving sustainable agricultural development, food security, and climate resilience. Agriculture, which employs over 60% of the continent’s population, plays a critical role in economic growth and poverty reduction. Yet, Africa’s food systems are under pressure from multiple challenges, including widespread food insecurity, malnutrition, environmental degradation, and vulnerability to climate change. Despite two decades of significant advancements through the implementation of the Comprehensive Africa Agriculture Development Programme (CAADP), the continent faces complex issues that demand a more transformative and systemic approach to agricultural development. The latest Africa Union 4th CAADP Biennial Review Report shows that none of the Member States are on-track towards achieving the CAADP Malabo commitments by 2025. The continent is doing particularly poorly on the ending hunger commitment, with none of the countries on-track towards achieving access to agriculture inputs and technologies, agricultural productivity, and food security and nutrition. The 2024 Africa Food Systems Forum (AFSF) saw a greater commitment from global leaders, Africa Heads of States, private sector, civil society, and international organizations to scale up investment in the transformation of Africa’s food systems to ensure food and nutrition security in Africa while creating jobs and opportunities youth and women. The year also saw intensification of engagements around the Post-Malabo discussion which have seen a strategic shift towards as a broader agri-food systems approach.